Perlindungan Hukum bagi Anak Pelaku Tindak Pidana Seksual menurut Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Ulfah Hidayah; M Taofik Makarao; Syarif Fadillah (Fakultas Hukum Universitas Islam As-Syafi'iyah, 2020)
Ulfa Hidayah Syarikatunnamla, 1220160028, Legal Protection for Child Actors Sexual Offenses According to Law No. 35 of 2014 regarding Child Protection. A child who has committed a criminal act of sexual need still obtain legal protection in all proceedings before or during the trial in the best interest of the child. The government has established Law Number 35 of 2014 concerning Child Protection as a strong legal basis to protect the rights of children as perpetrators. This research uses a qualitative descriptive research method, which is in the form of describing, analyzing and analyzing the applicable provisions, to provide an overview of how legal protection for child perpetrators of sexual crimes is linked to the Child Protection Act. The results of this study have illustrated that the Child Protection Law is good enough in terms of protecting children's rights and sanctions for children who violate the rules. It's just that what needs to be considered is the implementation, so that the regulations and their implementation can go walk side by side.